The Number of Interstitial Cells of Cajal Differs Among Different Subtypes of Achalasia and is Related to Patients' Prognosis. Issue 8 (24th August 2021) - Chen, Songfeng; Zhang, Mengyu; Liang, Mengya; Tan, Niandi; Cui, Yi; Wang, Jinhui; Xin, Xiangbin; Ye, Ziyin; Zhuang, Qianjun; Xiao, Yinglian
Abstract : INTRODUCTION: Achalasia is a primary esophageal motility disorder with heterogeneous manometric subtypes and prognosis, characterized by degeneration of the esophageal myenteric plexus, and reduction in interstitial cells of Cajal (ICCs). This study aimed to explore the histopathologic characteristics of lower esophageal sphincter (LES) muscle from patients with achalasia with different subtypes and different prognosis. METHODS: We examined specimens of LES muscle from 122 patients with achalasia who underwent peroral endoscopic myotomy and from 10 control patients who underwent esophagectomy for esophageal cancer. Hematoxylin–eosin staining was performed to assess inflammation infiltration, fibrosis, and atrophy. Specific immunohistochemical staining was performed to identify ICCs and neuronal nitric oxide synthase (nNOS). RESULTS: The number of ICCs in patients with type I achalasia was significantly lower than that in patients with type II achalasia, followed by that in control patients (type I vs type II vs control group= 0.4 vs 1.2 vs 9.5; P < 0.001). The number of nNOS-positive cells was significantly lower in patients with achalasia than that in control patients (type I vs type II vs control group = 0.0 vs 0.0 vs 8.0; P < 0.001). Nonrecurrent group had significantly more ICCs than recurrent group (type I: nonrecurrent vs recurrent = 1.0 vs 0.1; P = 0.010; type II: nonrecurrent vs recurrent = 2.0 vs 0.4; P = 0.004). DISCUSSION: ICCs and nNOS-positive cells reduced significantly in LES muscle of patients with achalasia. The number of ICCs differed among different achalasia subtypes and was related to patients' clinical prognosis.